Kontroversi Hukum Asuransi: Studi tentang Argumentasi Mustafa Ahmad al-Zarqa dalam Pembolehan Asuransi - Hasanudin Hasanudin (Al-Manahij: Jurnal Kajian Hukum Islam, 2018)
Insurance came to the Islamic world around the 19th century AD. As long as the insurance law in Islam is concerned, the contemporary Islamic scholars are divided into three groups. First, scholars who allow it absolutely; secondly, the ulama who forbid it absolutely; and thirdly, scholars who legalize social insurance and forbid commercial insurance. One of the contemporary scholars who justifies insurance is Muá¹£á¹afÄ Aá¸¥mad al-ZarqÄ', a prominent Islamic scholar of á¸¤anafi from Syria. The findings of this study are that in the perspective of Islamic legal theory the arguments of al-ZarqÄÊ¼ can be justified. The theory of Islamic law used by al-ZarqÄ' in examining insurance is the theory of ijtihad bi ar-ra'y by istiá¹£á¸¥ÄbÄ« and ta'lÄ«l methods. Al-Zarqa' views that insurance is a new contract that does not exist in Islamic jurisprudence. Every Muslim is allowed to create new contracts that have not existed before as long as there is no prohibition against them. Al-ZarqÄÊ¼ analogize the insurance with the existing contracts in Islamic jurisprudence, among which is the contract of muwaÌ„laÌ„h from Hanafite school of law, dÌ£amaÌ„n khatÌ£r al-á¹ariÌ„q from Hanafites, al-iltizaÌ„m wa al-waâ€™d al-mulzim in Malikites, and al-â€˜aÌ„qilah in Syafiâ€™ites.